2016
DOI: 10.1111/sed.12265
|View full text |Cite
|
Sign up to set email alerts
|

Complex coastal change in response to autogenic basin infilling: An example from a sub‐tropical Holocene strandplain

Abstract: Thick bay-fill sequences that often culminate in strandplain development serve as important sedimentary archives of land-ocean interaction, although distinguishing between internal and external forcings is an ongoing challenge. This study employs sediment cores, ground-penetrating radar surveys, radiocarbon dates, palaeogeographic reconstructions and hydrodynamic modelling to explore the role of autogenic processes -notably a reduction in wave energy in response to coastal embayment infilling -in coastal evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 107 publications
(163 reference statements)
1
51
0
Order By: Relevance
“…A similar deceleration in shoreline growth at Pedro Beach, Australia, may be linked to changes in accommodation (Oliver et al, ). A possible concern is that the rates of strandplain progradation (0.4–1.8 m/year; Bristow & Pucillo, ; Brooke et al, ; Hein et al, ) are generally lower than those observed in our barrier island study sites. However, as we demonstrate through application of our model to Parramore Island, the model can be used at sites undergoing slower progradation (i.e., 0.16 m/year; Q S = 1.6 m/year), particularly if corresponding foredune fluxes are also low (i.e., Q D = 0.7 m/year).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…A similar deceleration in shoreline growth at Pedro Beach, Australia, may be linked to changes in accommodation (Oliver et al, ). A possible concern is that the rates of strandplain progradation (0.4–1.8 m/year; Bristow & Pucillo, ; Brooke et al, ; Hein et al, ) are generally lower than those observed in our barrier island study sites. However, as we demonstrate through application of our model to Parramore Island, the model can be used at sites undergoing slower progradation (i.e., 0.16 m/year; Q S = 1.6 m/year), particularly if corresponding foredune fluxes are also low (i.e., Q D = 0.7 m/year).…”
Section: Discussionmentioning
confidence: 64%
“…The planar, near‐horizontal transgressive surface upon which Parramore Island prograded makes it an ideal site to record externally mediated changes in shoreface sediment fluxes, as accommodation effects such as growth into an offshore‐deepening basin (e.g., Bristow & Pucillo, ) or into an infilling bay (e.g., Hein et al, ) are minimal. Hence, the rate of progradation of this barrier island should reflect only the rate of sea level rise and net (longshore and cross‐shore inputs minus long‐term erosion) external sediment fluxes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nielsen et al, 2017;Rodriguez and Meyer, 2006;van Heteren et al, 2000), (3) quantify sediment budgets (Bristow and Pucillo, 2006;Dougherty et al, 2015;van Heteren et al, 1996), and (4) decipher coastal 30 evolution (e.g. Barboza et al, 2009;Costas and FitzGerald, 2011;Hein et al, 2016). Combining GPR, OSL, and LiDAR (GOaL) on certain systems offers the possibility to determine a history of storms, sea level, sediment supply, and their impact on shoreline evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Because GPR is sensitive to subtle changes in the subsurface, the record must be ground-truthed using cores, augers, or outcrops, in order to verify 10 barrier facies and boundaries (e.g. Costas and FitzGerald, 2011;Hein et al, 2013;Hein et al, 2016). Additionally, topographic profiles of the present-day beach and sediment samples from each facies should be collected, preferably capturing both storm and swell geometry and sedimentology.…”
mentioning
confidence: 99%